FRI0510 Correlation of the routine assessment of patient index data (RAPID-3) with other psoriatic arthritis composite disease activity measures in patients receiving adalimumab. (15th June 2017) - Mease, PJ; Chen, S; Ganz, F; Tillett, W
Abstract : Background: There is increased interest across rheumatologic disease to utilize patient (pt)-reported outcomes (PROs) in disease assessment. Several measures entirely derived from PROs, such as the 3-component routine assessment of pt index data (RAPID-3), have been shown to be closely correlated with physician rheumatoid arthritis assessments using traditional composite scores. 1 Objectives: To assess the correlation between the RAPID-3 and other psoriatic arthritis (PsA) composite indices [eg, disease activity index for PsA (DAPSA), minimal disease activity (MDA)] in pts with PsA receiving adalimumab (ADA) or placebo (PBO). Methods: This post hoc analysis used data from the ADEPT trial, which included pts with active PsA despite prior DMARD therapy who were randomized to receive ADA or PBO for 24 weeks (wks). Mean RAPID-3 was summarized by visit for each treatment group. Correlations between RAPID-3 and DAPSA over time were assessed through Pearson and Spearman coefficient. Pts were categorized at wk 24 according to DAPSA [Remission: ≤4; low disease activity (LowDA): >4 – ≤14; moderate disease activity (ModDA): >14 – ≤28; high disease activity (HighDA): >28) and MDA [achievement of 5 of 7 or the more stringent 7 of 7 criteria (very low disease activity [VLDA]): yes, no], and assessed for the numbers of pts in each respective RAPID-3 disease activity state (Remission: ≤3; LowDA: >3 – ≤6; ModDA: >6 – ≤12; HighDA: >12). The Kappa statistic was used to describe the agreement between the numbers of pts in respective disease activity categories by RAPID-3, DAPSA, and MDA. Data were as observed. Results: Amongst the 151 and 162 pts randomized to receive ADA and PBO, respectively, both groups exhibited HighDA when assessed by RAPID-3 [13.1 for both groups; 55% (ADA) and 54% (PBO) in HighDA]. At wk 24, mean RAPID-3 remained in HighDA for the PBO group (12.6), whereas it decreased to a state of LowDA (6.8) in those receiving ADA. Following 24 wks of treatment, 39% and 24% in the ADA group were in remission by RAPID-3 and DAPSA, respectively. Fewer pts in the PBO group were in remission by either definition at wk 24 (8% and 3%, respectively). At baseline, there was moderate correlation between RAPID-3 and DAPSA in both treatment groups (ADA: 0.512; PBO: 0.510). At wk 24, the correlations in both treatment groups increased, with the correlation observed in the ADA group outpacing the PBO group (ADA: 0.721; PBO: 0.590). Similarly, disease activity categorizations by RAPID-3 correlated with DAPSA and MDA categorizations (Table). Conclusions: In a PBO-controlled trial of ADA in pts with PsA, there was good correlation between disease activity captured by pt's self-assessment, via the RAPID-3, and physician assessment, underscoring the potential utility of pt-derived measures in assessing disease activity. References: Pincus and Sokka. Best Pract Res Clin Rheumatol 2007;21(4):733–53. Acknowledgements: AbbVie: study (NCT00646386 ) sponsor, contributed to design, data collection, analysis, interpretation, and abstract writing, review, and approval. Medical writing: Ben Wolfe of AbbVie. Disclosure of Interest: P. Mease Grant/research support from: AbbVie, Amgen, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, Sun Pharma, and UCB, Consultant for: AbbVie, Amgen, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, Sun Pharma, and UCB, Speakers bureau: AbbVie, Amgen, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, Sun Pharma, and UCB, S. Chen Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., F. Ganz Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., W. Tillett Grant/research support from: AbbVie, Celgene, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Celgene, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene, Novartis, Pfizer, and UCB